DETERMINANTS OF THE PROFITABILITY OF COMMERCIAL BANKS IN ETHIOPIA - Muktar Abdela Shifa; Kenenisa Lemmi Debela; Endalew Gutu Tarfa (Copernican Journal of Finance & Accounting, 2020)
The healthiness of the banks is critical because they are highly fragile, vulnerable and closely integrated with other sectors. One way of testing the healthiness of the banks is through the measure of their profitability. Profitability is the primary objective of any business including commercial banks. Profitable banks can withstand any negative shocks and stabilize the whole financial sector. The main objective of this study was to analyze the determinants of the profitability of commercial banks in Ethiopia. To achieve this objective a secondary source balanced panel data of ten years from nine commercial banks were used, and internal determinants; business mix indicators, risk aversion index, management efficiency, liquidity risk, bank size, and external determinants; ownership, market concentration, and GDP, were regressed against return on asset by using the pooled OLS technique. Results indicated that internal determinants were more important than external factors. Thus business mix indicators, risk aversion index, management efficiency, liquidity risk and bank size had a significant effect on the return on asset, whereas except ownership other external determinants, i.e. market concentration and GDP were insignificant to determine return on assets of Ethiopian commercial banks. Finally bank managers were recommended to rely on the debt financing sources paying a due attention to the optimal levels, mobilize more deposits, extend loan provision and expand business mixes services.